Primary Auditory Cortex is Required for Anticipatory Motor Response. (4th April 2017) - Li, Jingcheng; Liao, Xiang; Zhang, Jianxiong; Wang, Meng; Yang, Nian; Zhang, Jun; Lv, Guanghui; Li, Haohong; Lu, Jian; Ding, Ran; Li, Xingyi; Guang, Yu; et al.
Abstract: The ability of the brain to predict future events based on the pattern of recent sensory experience is critical for guiding animal's behavior. Neocortical circuits for ongoing processing of sensory stimuli are extensively studied, but their contributions to the anticipation of upcoming sensory stimuli remain less understood. We, therefore, used in vivo cellular imaging and fiber photometry to record mouse primary auditory cortex to elucidate its role in processing anticipated stimulation. We found neuronal ensembles in layers 2/3, 4, and 5 which were activated in relationship to anticipated sound events following rhythmic stimulation. These neuronal activities correlated with the occurrence of anticipatory motor responses in an auditory learning task. Optogenetic manipulation experiments revealed an essential role of such neuronal activities in producing the anticipatory behavior. These results strongly suggest that the neural circuits of primary sensory cortex are critical for coding predictive information and transforming it into anticipatory motor behavior.